DEVELOPMENT OF 2D ANIMATION LEARNING MEDIA ON TRAVELING AND STATIONARY WAVE MATERIAL FOR GRADE XI HIGH SCHOOL: PENGEMBANGAN MEDIA PEMBELAJARAN ANIMASI 2D PADA MATERI GELOMBANG BERJALAN DAN STASIONER KELAS XI SMA - Muhamad Apriansyah Ramadhan; Hadi Nasbey; Sunaryo (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2025)
This study aims to create 2D animations as an effective learning medium for the subjects of TravelingWaves and Standing Waves for 11th-grade high school students. These animations are designed to be aneffective learning resource and to enhance the learning process. The advantage of the developed productlies in its ability to present complex concepts in a visually appealing and easily understandable manner,thereby improving the student’s learning experience. This research is expected to provide validated,effective, and engaging learning media for the study of Traveling Waves and Standing Waves. Theresearch methodology used is R&D (Research and Development), following the 4D development model(Define, Design, Develop, Disseminate). The creation of the animations involves the use of varioussoftware such as Manim, OpenToonz, GIMP, Inkscape, and LibreOffice Draw. The developedanimations then go through a validation process by media experts, subject matter experts, and learningexperts to ensure their feasibility. The research results are obtained from trials conducted with 11thgradehigh school students. These trials are designed to evaluate the effectiveness of the animations as alearning tool. Feedback from these trials is used to further refine the animations.